2022
DOI: 10.3390/mi13081217
|View full text |Cite
|
Sign up to set email alerts
|

Q-Factor Enhancement of Coupling Bragg and Local Resonance Band Gaps in Single-Phase Phononic Crystals for TPOS MEMS Resonator

Abstract: This paper presents a type of single-phase double “I” hole phononic crystal (DIH-PnC) structure, which is formed by vertically intersecting double “I” holes. By using the finite element method, the complex energy band curve, special point mode shapes, and different delay lines were calculated. Numerical results showed that DIH-PnC yielded ultra-wide band gaps with strong attenuation. The formation mechanism is attributed to the Bragg-coupled local resonance mechanism. The effects of the pore width in DIH-PnC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Pandey et al designed a mesa around the resonator to reflect the elastic energy back to the resonator [ 18 ]. Using the band gap characteristics of phononic crystals (PCs) to suppress the anchor loss has attracted the attention of researchers [ 3 , 11 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, Zhu et al used a two-dimensional stomatal PCs unit cell to increase the Q to twice the original [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pandey et al designed a mesa around the resonator to reflect the elastic energy back to the resonator [ 18 ]. Using the band gap characteristics of phononic crystals (PCs) to suppress the anchor loss has attracted the attention of researchers [ 3 , 11 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, Zhu et al used a two-dimensional stomatal PCs unit cell to increase the Q to twice the original [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ardito et al used a one-dimensional PCs structure to increase the Q by several times [ 24 ]. Other shapes, such as rings [ 27 ], cross-like holes [ 13 ], fractals [ 14 ], Spider Web-Likes [ 15 ], cross-section connections [ 25 ], double “I” holes [ 26 ], and snowflakes [ 28 ] have also been reported. At present, Yinjie Tong has increased the Q of Pillar-Based PCs by 54% in the UHF range [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workie et al studied a prism-shaped PnC and found that the unloaded quality factor (Q u ) of a traditional resonator was increased by 1.7 times (for a butterfly rounded-edge resonant structure), 2.78 times (for a PnC deployed on the tether), and 2.8 times (for a PnC deployed on the anchor), respectively [ 13 ]. In 2022, Li et al investigated a double “I” -hole PnC, and the results showed that the Q anchor of the resonator was 20,425.1% higher than that of a traditional resonator [ 14 ]. In 2023, Awad et al designed a reem-shaped PnC and deployed it on the anchored boundary of a resonator, resulting in an increase of 33.3 times in the Q anchor value and 1.2 times in the Q u value, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%